INCREASING SKILLS WRITING NEGOTIATION TEXT SMK STUDENTS THROUGH INDUCTIVE APPROACH - Jesika Aprilia; Dida Firmansyah (JLER (Journal of Language Education Research), 2018)
Negotiations on some parties who have problems trying to resolve differences that exist by way of dialogue to get a mutual agreement and without any party who feel harmed. Among the areas that use the text of negotiation in the field of politics, education, trade, events and so forth. The inductive approach is the process of thinking from the particular to the general and the students look for the characteristics or specific properties of various phenomena, then draw conclusions. if in the teaching of the teacher in teaching does not give the students a full discovery, prove their own principles, laws, and so on the learning materials to be reviewed. The inductive approach requires students to be more active, creative, critical during learning performances and the role of teachers as motivators and facilitators so that students' communication and problem-solving skills develop. With the application of the inductive approach is expected to improve students' writing text negotiation skills, because through the inductive approach of students will be easier in learning writing negotiating text.